Molecular genetic testing for hereditary ataxia: What every neurologist should know - Wallace, Stephanie E. (Neurol Clin Pract, 2018)
PURPOSE OF REVIEW: Because of extensive clinical overlap among many forms of hereditary ataxia, molecular genetic testing is often required to establish a diagnosis. Interrogation of multiple genes has become a popular diagnostic approach as the cost of sequence analysis has decreased and the number of genes associated with overlapping phenotypes has increased. We describe the benefits and limitations of molecular genetic tests commonly used to determine the etiology of hereditary ataxia. RECENT FINDINGS: There are more than 300 hereditary disorders associated with ataxia. The most common causes of hereditary ataxia are expansion of nucleotide repeats within 7 genes: ATXN1, ATXN2, ATXN3, ATXN7, ATXN8, CACNA1A (spinocerebellar ataxia type 6), and FXN (Friedreich ataxia). Recent reports describing the use of clinical exome sequencing to identify causes of hereditary ataxia may lead neurologists to start their clinical investigation with a less sensitive molecular test providing a misleading “negative” result. SUMMARY: The majority of individuals with hereditary ataxias have nucleotide repeat expansions, pathogenic variants that are not detectable with clinical exome sequencing. Multigene panels that include specific assays to determine nucleotide repeat lengths should be considered first in individuals with hereditary ataxia.